Alkoholisis minyak biji kepuh (sterculia foetida l.) Pada tekanan lebih dari satu atmosfer dengan katalisator buangan proses perengkahan minyak bumi Pertamina unit II Palembang=Alkoholysis of Kepuh (Sterculia Foetida L. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
Kepuh (Sterculia Foetida L.) seed oil is not utilized yet. Therefore, it should be processed to produce valuable product. One of the possible methods is alcoholysis with wasted solid catalyst obtained from Pertamina Unit II located in Palembang, as catalyst. With this process some benefits might be obtained from'these wastes. The alkoholysis of kepuh seed oil with etanol and reactivated used solid catalyst at higher pressure was accomplished in an autoclave provided with manometer, thermometer, sampling device, heater, and mixer. The experiment was started by filling the autoclave with kepuh seed oil, alcohol, and the catalyst, then the heater and the mixer were switched on. Samples were taken out at 10 minutes intervals, and after being separated, the bottom layer was analyzed in order to determine its glycerol content using acetin method. By raising the temperature, catalyst concentration, rate of mixing, and ethanol-oil ratio, the glyceride conversion increased. From the value of k' , Reynolds index, the change of k' with 10Â°C increase of temperature, and the value of the activation energy, it seemed that chemical reaction controlled the process. The alcoholysis of kepuh seed oil followed pseudo first order reaction with respect to the glyceride concentration. The equation of the reaction rate constant, k' , can be presented as : = 1659.2152 e46641'741 T (7.4976(10') + 4.6455(10) H} N "529P 0.'524, with experimental errors of Â± 13.66 % for V , and a deviation of x of Â± 8.89 %. The relative favorable process conditions were 60 minutes of reaction time, temperature of 110Â°C, catalyst concentration of 2 %, mixing velocity of 310 rpm, and alcoholâoil ratio of 6 mgek/mgek. Under this a condition the conversion was 70.91 %.